Macroeconomics for public sector managers - Adeyemo, O. A.; National Centre for Economic Management and Administration (Nigeria) (Ibadan, Nigeria : National Centre for Economic Management and Administration, 1991)
This report is the outcome of the macroeconomic course on the management of Nigeria's reform programme which was delivered by the Centre at Ibadan from February 11- March 27, 1991.
An NCEMA Training Programme Report, March1991
Includes bibliographical references.
rpm 22/01/2019
Loans
Keywords: Managerial economics; Macroeconomics; Nigeria